Fingerprint Template Protectionsthrough Various Pattern Transformation Approaches: A Review - K, Kanagalakshmi1; Antony, Joycy K (International Journal of Computer Sciences and Engineering, 2019)
Biometric Templates are majorly used as an authentication and identification metric of a person in different industries. The Biometric templates are generated through various mechanisms like key, index and transformation based. This paper focuses on a study of fingerprint Biometric and various existing pattern transformation approaches based on fingerprint.